Evaluating the SOS suicide prevention program: a replication and extension - Glanovsky Jaime; Schilling Elizabeth A; James Amy; Aseltine Robert H (BMC, 2007)
Abstract Background Suicide is a leading cause of death for children and youth in the United States. Although school based programs have been the principal vehicle for youth suicide prevention efforts for over two decades, few have been systematically evaluated. This study examined the effectiveness of the Signs of Suicide (SOS) prevention program in reducing suicidal behavior. Methods 4133 students in 9 high schools in Columbus, Georgia, western Massachusetts, and Hartford, Connecticut were randomly assigned to intervention and control groups during the 2001-02 and 2002-03 school years. Self-administered questionnaires were completed by students in both groups approximately 3 months after program implementation. Results Significantly lower rates of suicide attempts and greater knowledge and more adaptive attitudes about depression and suicide were observed among students in the intervention group. Students' race/ethnicity, grade, and gender did not alter the impact of the intervention on any of the outcomes assessed in this analysis. Conclusion This study has confirmed preliminary analysis of Year 1 data with a larger and more racially and socio-economically diverse sample. SOS continues to be the only universal school-based suicide prevention program to demonstrate significant effects of self-reported suicide attempts in a study utilizing a randomized experimental design. Moreover, the beneficial effects of SOS were observed among high school-aged youth from diverse racial/ethnic backgrounds, highlighting the program's utility as a universal prevention program. Trial registration clinicaltrials.gov NCT000387855.